Manajemen Madrasah dalam Membentuk Budaya Sehat Melalui Pengelolaan Sampah - Suharto, Muhammad; Sulistiyono, Sulistiyono (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2021)
The focus of this research is 1) How is Madrasah Management in Forming a Healthy Culture through Waste Management at MI. Nurul Huda Sumput Driyorejo Gresik? 2) What is the Process of Madrasahs in Forming a Healthy Culture through Waste Management in MI. Nurul Huda Sumput Driyorjo Gresik? 3) What are the results of Madrasah Management in Forming a Healthy Culture through Waste Management in MI. Nurul Huda Sumput Driyorjo Gresik? Meanwhile, the goal of Madrasah Management is to Establish a Healthy Culture through Waste Management in Mi. Nurul Huda Sumput Driyorejo Gresik is 1) To know Madrasa Management in Establishing a Healthy Culture through Waste Management at MI. Nurul Huda Sumput Driyorjo Gresik. 3) To find out the results of madrasa management in forming a healthy culture through waste management in MI. Nurul Huda Sumput Driyorjo Gresik.The type of research used is qualitative with a case study approach. The results of this research are: 1) Madrasah Program which consists of Waste Management, Work Program of Principals, Teachers and Education Personnel of Madrasah residents 2) The process carried out is training, comparative studies and collaboration with related parties 3) The results realized include the existence of madrasa work programs, school principals and institutional committees/management. There are rules related to cleanliness in the madrasa and a culture of healthy behavior is built for students.